Sustainable citric acid production from CO2 in an engineered cyanobacterium - Zhang, Lifang; Bryan, Samantha J.; Selão, Tiago Toscano (Frontiers in Microbiology, 2022)
Citric acid is one of the most widely used organic acids in the world, with applications ranging from acidity regulation in food and beverages to metal chelation in hydrometallurgical processes. Most of its production is currently derived from fermentative processes, using plant-derived carbon feedstocks. While these are currently dominant, there is an increasing need to develop closed-loop production systems that reduce process carbon footprint. In this work we demonstrate for the first time that an engineered marine cyanobacterium Synechococcus sp. PCC 7002 can be used as a sustainable chassis for the photosynthetic conversion of CO2 to citric acid. Decreased citric acid cycle flux, through the use of a theophylline-responsive riboswitch, was combined with improved flux through citrate synthase and enhanced citric acid excretion, resulting in a significant improvement to citric acid production. While allowing citrate production, this strategy induces a growth defect which can be overcome by glutamate supplementation or by fine-tuning aconitase levels, resulting in an increase in production relative to WT of over 100-fold. This work represents a first step towards sustainable production of a commodity organic acid from CO2.